2018
DOI: 10.1177/1558944718770210
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Image Quality and Radiation Exposure Between the Mini C-Arm and the Standard C-Arm

Abstract: Due to its improved image quality and overall practicality, the mini C-arm is recommended for hand surgical procedures. To ensure that the surgeons' radiation exposure is not exceeding the safety limits, monitoring radiation exposure using mini C-arms with flat panel technology during surgery should be done in a future clinical study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Singer et al 19 used a cadaveric setup to measure direct patient radiation exposure and found that exposure using the mini c-arm was 53% to 70% greater than that using the conventional c-arm. Similarly, van Rappard et al 20 reported that, although image quality was significantly improved with the mini c-arm, the patients' entrance dose was 10 times higher for the mini c-arm as compared with its conventional counterpart. Conversely, the mini c-arm was found to be associated with a statistically significant reduction in DAP in foot and ankle surgery 21 as well as a reduction in occupational exposure to the surgeon and operating room staff in a cadaveric wrist model 22 .…”
Section: Discussionmentioning
confidence: 92%
“…Singer et al 19 used a cadaveric setup to measure direct patient radiation exposure and found that exposure using the mini c-arm was 53% to 70% greater than that using the conventional c-arm. Similarly, van Rappard et al 20 reported that, although image quality was significantly improved with the mini c-arm, the patients' entrance dose was 10 times higher for the mini c-arm as compared with its conventional counterpart. Conversely, the mini c-arm was found to be associated with a statistically significant reduction in DAP in foot and ankle surgery 21 as well as a reduction in occupational exposure to the surgeon and operating room staff in a cadaveric wrist model 22 .…”
Section: Discussionmentioning
confidence: 92%
“…Gieroba TJ et al demonstrated that since the surgeon can easily operate mini C-arm without a radiographer, it reduces surgery delays and saves about 4 minutes of operation time per surgery (15). Although the mini C-arm fluoroscopy device has been promoted mainly due to its easy mobility, decreased cost, and its usage in taking images from smaller parts of the body in the operation room or emergency department (16,17), recently van Rappard JRM et al indicated that the image quality is significantly better for the mini C-arm in comparison with the standard C-arm in hand surgeries (18).…”
Section: Physical Aspectmentioning
confidence: 99%
“…It is a commonly used surgical auxiliary tool in clinical orthopedics. The main uses include assisting in fracture reduction and xation during orthopedic surgery, assisting in implanting a pacemaker, assisting in extracting foreign bodies from the body, assisting in part of angiography and interventional operations, cooperating with an ozone machine to treat pain, cooperating with small needle-knife treatment, assisting gynecological tubal guidance surgery, and so forth [2][3][4][5][6]. It has the advantages of low infection risk, small footprint, and easy movement.…”
Section: Introductionmentioning
confidence: 99%